REDUCER RESONANT ELECTRIC STEERING - Бондарчук, П. С. (Science-based technologies, 2015)
The general requirements to a reducer of the resonant electric steering drive (RESD) taking into account its specifics the most important of which are high efficiency in both directions, a high specific torque and large gear number in small volume are stated. The short review of literature on a subject is carried out, the main types of the modern mechanical transmissions are given, the analysis of suitability of each of them for application in the resonant steering drive is carried out and the most suitable – wave transmission with the intermediate bodies of rolling is selected. The principle of action of this mechanical transmission is considered and the concept of the steering drive in overall dimensions of a support assembly of a aerodynamic rudder which in the best way is suitable for RESD on the basis of this transmission is discussed. Results of calculation of mass and overall dimensions of a reducer, its specific indexes and an assessment of an achievable technical level of RESD on the basis of the selected transmission are given.